Phenomenon of an Irrational in Eastern Direction in Thinking - Kortunov, Vadim V.; Gozalova, Marina R. (International Journal of Criminology and Sociology, 2022)
Indian mythology and the Vedic image of the world built on its basis are of exceptional importance for understanding the entire Eastern culture. The mythological complex of Indian representations is the most ancient (researchers attribute its formation to the III millennium BC) and surprisingly persistent. The Vedic image of the world combines the features of proper mythology and religion and philosophy; it becomes the initial model for the formation of later religious and philosophical doctrines. Recall that it was the Vedic image of the world that formed the Brahmanism ideology prevailing in Ancient India and then formed the foundation of modern Hinduism through a modification of the Brahmin doctrine. Moreover, even religious-philosophical systems opposed to Brahmanism, such as Jainism, Bhagavatism, Buddhism, which questioned Rigveda and other Samhitas’s sanctity, maintained a standard worldview continuity and solidarity with the fundamental images of the Vedic world model. Of course, Indian mythology, especially at the early stages of its formation, has much in common with mythological representations of other peoples of the world. At a particular stage in the development of mythic consciousness, we can everywhere find syncretic and anthropomorphic motifs, echoes of totemism or animism, the influence of matriarchy, and, of course, the tendency to overcome polytheistic traditions and the tendency to theistic monism. However, in the East, all these elements of mythological consciousness acquired an exceptional fundamental sound, making it possible to raise the question of the specifically Eastern way of world relations and the key importance of Vedic images in the general model of the world built by the East.